Safety of quadrivalent meningococcal conjugate vaccine in infants and toddlers 2 to 23-months old. Issue 2 (10th January 2020) - Becerra-Culqui, Tracy A.; Sy, Lina S.; Ackerson, Bradley K.; Slezak, Jeff M.; Luo, Yi; Fischetti, Christine A.; Ohadike, Yvonne U.; Curina, Carlo; Pellegrini, Michele; Solano, Zendi; Tartof, Sara Y.; Tseng, Hung Fu
Highlights: About 42% of infants who received MenACWY-CRM had an indicated high-risk condition. After vaccination, 29% had an incident condition in emergency/hospital visits. Fever and upper respiratory infections were most common. Incident emergency/hospital visit rates were comparable to background rates. There are no safety concerns from the conduct of this post-licensure safety study. Abstract: Introduction: The quadrivalent meningococcal conjugate vaccine MenACWY-CRM is recommended for 2–23 month-old infants/toddlers at increased risk for meningococcal disease. This study adds to the current knowledge of MenACWY-CRM safety among this age group in a clinical care setting. Methods: Kaiser Permanente Southern California members aged 2–23 months who received MenACWY-CRM between July 2014 and June 2017 were included. Electronic health records were searched for emergency department ( ED) and hospitalization encounters, and diagnoses associated with these visits up to 6 months after each dose. Results: There were 138 infants/toddlers who received MenACWY-CRM, with 59.4% being African American and 66.7% receiving only one dose. Most infants either had a high-risk condition (i.e., anatomic/functional asplenia or DiGeorge syndrome) (42.0%), or a travel indication (54.3%). The incidence rate of ED visits was 0.6/person-year (95% confidence interval [CI]: 0.5–0.8), 0.4/person-year (CI: 0.3–0.5) for hospitalizations, and 0.1/person-year (CI: 0.1–0.3) for ED to hospital transfers. Overall, 29.0% of recipients had an incident diagnosis in the ED or hospital setting. Fever and acute upper respiratory infections were the most common diagnoses, with 46 out of 47 diagnoses occurring among infants with high-risk conditions. Conclusions: Data from this descriptive observational study do not suggest safety concerns associated with MenACWY-CRM when used as part of clinical care of 2–23 month-old infants/toddlers indicated for vaccination.